Epiperipatus puri sp. nov., a new velvet worm from Atlantic Forest in Southeastern Brazil (Onychophora, Peripatidae) - Cristiano Sampaio Costa; Amanda Cruz Mendes; Alessandro Ponce de Leão Giupponi (PeerJ, 2023)
Epiperipatus ohausi (Bouvier, 1900) is the first species known from Rio de Janeiro, and more than 120 years later a new species is described in the state of Rio de Janeiro (RJ). In this study, we describe the second species in the state of Rio de Janeiro, which we are naming in honor of the indigenous population called puri who resided in southeastern coastal Brazil. The species can be diagnosed mainly by large dorsal primary papillae close to the insertion of the legs drawing a light band from the anterior to the posterior region of the body, and large dorsal primary papillae alternating on the dorsal plicae. Moreover, they are recognized in vivo by the color of the diamond-shaped marks brownish orange on the dorsal portion of the body. Epiperipatus puri sp. nov. morphologically seems to be related to Epiperipatus acacioi (Marcus & Marcus, 1995) by the shape of the primary papillae apical piece and to E. ohausi by the resemblance of dorsal papillae. The phylogeny shows a close relationship between the new species and E. ohausi in a clade with a still undescribed species from Rio de Janeiro, Brazil located within the Atlantic Forest, one of the most threatened biomes in the world.